2020
DOI: 10.1371/journal.pone.0234508
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis and characterization of neurotropic dengue virus 2 cosmopolitan genotype isolated from the cerebrospinal fluid of encephalitis patients

Abstract: Dengue virus (DENV) infection remains a major public health concern in many parts of the world, including Southeast Asia and the Americas. Sri Lanka experienced its largest dengue outbreak in 2017. Neurological symptoms associated with DENV infection have increasingly been reported in both children and adults. Here, we characterize DENV type 2 (DENV-2) strains, which were isolated from cerebrospinal fluid (CSF) and/or serum of patients with dengue encephalitis. Acute serum and CSF samples from each patient wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…Another possible mechanism is a direct CNS invasion by the dengue virus through the compromised blood-brain barrier. The direct neurotropism of the dengue virus has recently been illustrated with the isolation of the virus RNA in the CSF, also evidenced in our case report [ 16 ].…”
Section: Discussionsupporting
confidence: 62%
“…Another possible mechanism is a direct CNS invasion by the dengue virus through the compromised blood-brain barrier. The direct neurotropism of the dengue virus has recently been illustrated with the isolation of the virus RNA in the CSF, also evidenced in our case report [ 16 ].…”
Section: Discussionsupporting
confidence: 62%
“…In our previous study on this outbreak 14, we reported the detection of cosmopolitan genotype of DENV-2 (74%) and genotype I of DENV-4 (1%). In addition, we also reported the isolation of a neurotropic DENV-2 cosmopolitan genotype from the cerebrospinal fluid of encephalitis patients (20). In the present study, we described the emergence of genotype I of DENV-3 that was first seen in Sri Lanka during 2017-2018.…”
Section: Discussionsupporting
confidence: 58%
“…Amino acid variants were detected using Lofreq [ 25 ] and Varscan v2.4.3 [ 26 ], and the results were counter-checked with Pilon [ 27 ], V-phaser-2 [ 28 ], SNVer, and freebayes [ 29 ]. SAMtools v1.9 was then used to generate the consensus sequence [ 30 ]. Pre-processing of the data was performed using GATK v3.8.1 and Picard v2.20 [ 30 ].…”
Section: Methodsmentioning
confidence: 99%